2018
DOI: 10.1038/s41598-018-20541-8
|View full text |Cite
|
Sign up to set email alerts
|

Ormeloxifene-induced unfolded protein response contributes to autophagy-associated apoptosis via disruption of Akt/mTOR and activation of JNK

Abstract: Autophagy, a regulated nutrient recycling program can affect both cell survival and cell death. Here, we show that Ormeloxifene (ORM), a selective estrogen receptor modulator approved for oral contraceptive use induces autophagic flux in ovarian cancer cells, which is activated by an ER stress response upstream of autophagy. The ER stress response is characterized by activation of IRE1α, PERK and ATF6 and is under regulation of JNK. Pharmacological inhibition of either autophagy or ER stress increased cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Currently, staining cells with acid‐labeled MDC is another rapid method for assessing autophagic activity . We herein continued to use the MDC dye to capture the fluorescent signals of MOMI‐1‐treated A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, staining cells with acid‐labeled MDC is another rapid method for assessing autophagic activity . We herein continued to use the MDC dye to capture the fluorescent signals of MOMI‐1‐treated A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The serine/threonine kinase mechanistic target of rapamycin (mTOR) functions as a mediator of cell survival, which is believed to be oncogenic [ 23 ]. The activation of AMPK might have a negative regulatory effect on mTOR expression, which is known to be resistant to apoptosis by regulating the activation of the caspase cascade and autophagy [ 24 , 25 ]. The results of this study showed that baicalin activated the SIRT1 / AMPK signaling, which further inhibited the phosphorylation of mTOR, resulting in an increase in apoptosis of human NSCLC cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is formed by double membrane vesicles and lysosomes, namely the autophagy body, which swallows cell damaged or harmful protein, organelles and complexes and the damaged organelles and protein is degraded by autophagy body. Although autophagy protects both normal and cancer cells from apoptosis, especially in the environment of cytotoxicity, malnutrition and other stimuli, when exceeding a certain limit, autophagy can cause apoptosis of normal and cancer cells [4042]. Autophagy can generally be divided into at least three major categories: macrophage, micro-autophagy and chaperone-mediated autophagy [43].…”
Section: Jnk and Ovarian Tumor: Role In The Deathmentioning
confidence: 99%